Leading with soul : an uncommon journey of spirit - Bolman, Lee G.; Deal, Terrence E. (San Francisco : Jossey-Bass Publishers, 1995)
"Inspired by the works of such visionary writers as M. Scott Peck and Max De Pree, authors Lee Bolman and Terry Deal have crafted a powerful story of one beleaguered executive's quest for passion and purpose in work and in life. Leading with Soul teaches that the heart of true leadership can only be found in the heart of a leader." "This contemporary parable chronicles the journey of Steve, a dispirited leader in search of something deeper and more satisfying than a preoccupation with the bottom line. He seeks answers from Maria, a sage whose wisdom was forged in her own hard-won business career. Although Maria's initial questions seem far afield from business, Steve unexpectedly discovers the true meaning of leadership. By rediscovering his own soul, he learns how to ignite the spirit of his organization."--BOOK JACKET.
Introduction : leadership and the meaning of life -- The search. Chap. 1. The heart of leadership lives in the hearts of leaders -- Chap. 2. The human heart is more than a pump -- Chap. 3. The journey of a soul -- Chap. 4. Discovering new teachers -- Interlude : reclaiming your soul -- Conviction. Chap. 5. A place to start -- Chap. 6. Vicissitudes of the journey -- Interlude : leaning into your fear -- Gifts. Chap. 7. Gifts of leadership -- Chap. 8. Authorship -- Chap. 9. Love -- Chap. 10. Power -- Chap. 11. Significance -- Interlude : community and the cycle of giving -- Sharing. Chap.12. Summoning the magic of stories -- Chap. 13. Lifting our voices in song -- Chap. 14. Celebrating shared icons -- Interlude : expressing the spirit -- A new life. Chap. 15. The twilight of leadership -- Chap. 16. Deep refuge -- Interlude : the cycle of the spirit -- Chap. 17. The legacy -- Afterword : continuing a spirited dialogue -- Notes -- Recommended readings -- Acknowledgments -- The authors.
Includes bibliographical references (p. 181-183).
Keywords: Leadership -- Moral and ethical aspects; Leadership -- Religious aspects; Leadership; Morals; Ethics; Religion